The Relationship between Self-Esteem and Depression in Adolescent Victims of Cyberbullying: A cross-sectional study - Tantri Utami; Yunani Sri Astuti (Indonesian Journal of Global Health Research, 2022)
Adolescence is a period of life that begins with biological changes during puberty and ends with the person entering the maturity stage. Along with the development of technology, teenagers have new media for bullying through SMS, cell phones, and the internet or referred to as cyberbullying. This study aims to determine the relationship between self-esteem and depression among adolescent victims of cyberbullying in Bogor. Method: Cross-sectional research method. Respondents were 116 junior high/high school students ranging from 13-18 years old in Bogor. The result shows that there is a relationship between self-esteem and depression in adolescent victims of cyberbullying (p-value = 0.036). The majority of adolescent cyberbullying victims are 12 years old, female, accessing the internet > 4-8 hours per day, mostly online opening social media, and the most frequently used social media is WhatsApp. Self-esteem is related to depression in adolescent victims of cyberbullying.